Pension provision recognition and assessment as a type of social capital in the context of the financial reporting socio-economic paradigm: international practice and national experience - Golochalova, Irina (Public Policy and Accounting, 2020)
In the context of the globalization of the economy, the activity of a business unit is considered as a system that includes economic, social and environmental components. As it is known, the result of the economic activity of a business unit is reflected in the financial statements, while the results of the effectiveness of the social subsystem are absent in it. In this context, the article explores the interpretation of social capital as a derivative of human capital and its socio-economic characteristics; in the context of the transition to the socio-economic paradigm of financial reporting, the identification of certain types of social capital of a business unit, and first of all, pension provision, is investigated; it also analyzes the mechanism for assessing the fulfillment of the retirement plan as a type of social capital in the framework of IFRS; the system of accounting and financial reporting of the Republic of Moldova is characterized in the context of the transition to a socio-economic concept of disclosing information on the value of a business unit; a model of accounting for the fulfillment of a retirement plan based on payments that meets the socio-economic paradigm of financial reporting is demonstrated.